Additional Intra- or Inter-session Balance Tasks Do Not Interfere With the Learning of a Novel Balance Task - Giboin, Louis-Solal; Gruber, Markus; Kramer, Andreas (Frontiers in Physiology, 2018)
Background: It has been shown that balance training induces task-specific performance improvements with very limited transfer to untrained tasks. Thus, regarding fall prevention, one strategy is to practice as many tasks as possible to be prepared for a multitude of situations with increased fall risk. However, it is not clear whether the learning of several different balance tasks interfere with each other. A positive influence could be possible via the contextual interference effect, a negative influence could be induced by the disruption of motor memory during consolidation or retrieval. Methods: In two three-week training experiments, we tested: 1) whether adding an additional balance task in the same training session would influence the learning of a balance task (first task: one-leg stance on a tilt-board (TB), six sessions, 15x20s per session; additional task: one-leg stance on a slack line (SL), same amount of additional training); 2) whether performing a different balance task (SL) in between training sessions of the first task (TB) would influence the learning of the first task. 26 healthy subjects participated in the first experiment, 40 in the second experiment. In both experiments the participants were divided into three groups, TB only, TB and SL, and control. Before and after the training period, performance during the TB task (3x20s) was recorded with a Vicon motion capturing system to assess the time in equilibrium. Results: Analyses of variance revealed that neither the additional intra-session balance task in experiment 1 nor the inter-session task in experiment 2 had a significant effect on balance performance improvement in the first task (no significant group × time interaction effect for the training groups, p=0.83 and p=0.82, respectively, only main effects of time). Conclusion: We could not find that additional intra- or intersession balance tasks interfere with the learning of a balance task, neither impairing it nor having a significant positive effect. This can also be interpreted as further evidence for the specificity of balance training effects, as different balance tasks do not seem to elicit interacting adaptations.